Transient Stability Analysis and Control of Distributed Photovoltaic Generators in the DC Distribution Network - He, Hanghang; Xia, Yanghong; Wei, Wei; Yang, Pengcheng (Frontiers in Energy Research, 2022)
As dominant power sources, the safe and reliable operation of photovoltaic (PV) generators is crucial for the DC distribution network. This study analyzes the transient stability of PV generators under large disturbances and proposes a variable parameter control strategy to suppress the transient instability. First, the transient stability of the PV generators is analyzed using the proposed power–voltage evolution curve. It is found that the PV side easily suffers undervoltage faults during the transient process, which will cause instability of the system. Based on the revealed unstable mechanism, the variable parameter control is proposed to enhance the transient stability of PV generators. Finally, all the findings have been validated by hardware-in-loop tests.